Peran Klub Motor Night Wolves dalam Konflik Rusia-Ukraina - Nasution, Fahmi Hawari; Paramasatya, Satwika (Journal of International Relations, 2020)
The Night Wolves Motorcycle Club, Russia’s first and largest Motorcycle Club, became one of the Non-state Actors who played a role in the Russia – Ukraine conflict in 2014. They succeeded in defending Crimean Peninsula from Ukraine Army and Ukraine Radical Nationalist who were willing to harm and kill any Crimean who support Russia. This becomes interesting to see how a Motorcycle Club could influence a whole city to join them in their social movement. This research aimed to explore the evolution of the Night Wolves Motorcycle Club from the protester of the government to a patriotic organization who support the government, describe the ideology of the Night Wolves motorcycle club, analyses the role of the Night Wolves motorcycle club in Ukraine, and explain the political process of Night Wolves as a non state actor. This research uses Descriptive Exploratory as the research method and uses theories of Social Movement and Political process. The result of this study indicate that Night Wolves’s parade over a few years back with Putin and several political figure has made their reputation as a patriotic organization and announced their ideology. By doing so, people of Crimea who had the same perspective were willing to join them. Night Wolves’s success in defending Crimea made their reputation in International World as a non-state actor who could intervene with international conflict. This shows the importance of Non-state actor in International Relations Study and the new type of non-state actor besides Non Governmental Organization and International Organization